KEBAHASAAN; BAHASA ARAB SEBAGAI BAHASA AL-QURAN - Dewi, Misnan Dewi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
AbstracThis paper aims to describe language; Arabic as the language of the Quran focuses on the hadith, the words of friends and scholars. The method used in this research is literature review. The focus of this research is language, which is detailed into four sub-focuses, namely (1) Sanad and Matan hadith, the words of friends and scholars about language., (2) Arabic as the language of the Qur'an, (3) the elements that become the specialty of Arabic as the language of the Qur'an, (4) Language skills and the relationship between Arabic language skills and learning outcomes of the hadith al-qur'an. Based on the results of the research and discussion, it can be concluded that learning Arabic is easier to memorize, understand, teach, and practice the contents of the Al-Quran. As the virtues of learning Arabic are very clear because Arabic is the language of the Qur'an and the Sunnah. This reason is a big reason why we have to learn Arabic besides on the other hand, including the language of international communication.Keywords: language and Arabic as the language of the Quran AbstrakTulisan ini bertujuan untuk mendeskripsikan tentang kebahasaan; bahasa arab sebagai bahasa al-quran berfokus pada hadits, perkataan sahabat dan ulama. Metode yang digunakan dalam penelitian ini adalah kajian pustaka. Fokus penelitian ini adalah kebahasaan,yang di rinci menjadi empat subfokus, yaitu (1) Sanad dan Matan hadits, perkataan sahabat dan ulama tentang kebahasaan., (2) Bahasa Arab sebagai Bahasa Al-Qur`an, (3) unsur-unsur yang menjadi keistimewaan bahasa arab sebagai bahasa al-qur’an, (4) Keterampilan berbahasa dan hubungan antara kemampuan berbahasa arab dengan hasil belajar al- qur’an hadits. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan bahwa dengan mempelajari bahasa arab lebih mudah menghafal, memahami, mengajarkan, dan mengamalkan isi Al-quran. Sebagaimana keutamaan-keutamaan mempelajari bahasa arab sangatlah jelas karena bahasa arab adalah bahasa Al-Qur`an dan As-Sunnah. Alasan ini yang menjadi alasan besar kenapa kita harus mempelajari bahasa arab selain disisi lain termasuk bahasa komunikasi internasional.Kata Kunci: kebahasaan dan bahasa arab sebagai bahasa al-quran